2022
DOI: 10.1038/s41467-022-30462-w
|View full text |Cite
|
Sign up to set email alerts
|

pH- and concentration-dependent supramolecular assembly of a fungal defensin plectasin variant into helical non-amyloid fibrils

Abstract: Self-assembly and fibril formation play important roles in protein behaviour. Amyloid fibril formation is well-studied due to its role in neurodegenerative diseases and characterized by refolding of the protein into predominantly β-sheet form. However, much less is known about the assembly of proteins into other types of supramolecular structures. Using cryo-electron microscopy at a resolution of 1.97 Å, we show that a triple-mutant of the anti-microbial peptide plectasin, PPI42, assembles into helical non-amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…The assembly of high aspect ratio structures does not necessarily designate amyloid fibril formation, [ 57,60–62 ] nor is there a single type of amyloid fibril, as polymorphism was previously shown in various systems. [ 15,33 ] Secondary structure characterization of the fibrils prepared through TCEP‐treatment of albumin confirmed the presence of beta‐sheet formation, which was further corroborated by ThT fluorescence measurements, validating the presence of amyloid‐like fibrils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly of high aspect ratio structures does not necessarily designate amyloid fibril formation, [ 57,60–62 ] nor is there a single type of amyloid fibril, as polymorphism was previously shown in various systems. [ 15,33 ] Secondary structure characterization of the fibrils prepared through TCEP‐treatment of albumin confirmed the presence of beta‐sheet formation, which was further corroborated by ThT fluorescence measurements, validating the presence of amyloid‐like fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…At acidic pH (3.6), below the isoelectric point of albumin, the surface charge of the fibrils was positive and fibrils were thicker. A more detailed structural analysis using X‐ray scattering [ 10,57 ] and/or electron microscopy techniques [ 60 ] could provide the atomic‐scale structure of the formed fibrils in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The reversal of helicity is frequently caused by alterations in pH, which induce changes in peptide conformation and interactions among amino acid-based building blocks. [47,48] Kanagaraj et al presented γ-cyclodextrin (γ-CDx) analogs as chiral hosts for the photocyclodimerization of 2-anthracenecarboxylic acid (AC). [35] The investigation focused on the impact of pH on the photoreactivity and the resulting stereochemistry of the photoproducts.…”
Section: Ph Valuementioning
confidence: 99%
“…The reversal of helicity is frequently caused by alterations in pH, which induce changes in peptide conformation and interactions among amino acid‐based building blocks. [ 47,48 ]…”
Section: Modulation Of Chirality In Supramolecular Self‐assembly Proc...mentioning
confidence: 99%
“…In general, proteins can self-assemble to supramolecular ordered structures upon various chemical and biological stimuli such as pH, enzyme, salts, etc., driven by noncovalent interactions. The as-formed self-assemblies can be used as highly biocompatible biofunctional materials, which demonstrate broad potential applications in drug delivery, tissue engineering, and so on. For example, Champion et al reported that the protein synthesized from elastin-like polypeptide could arrange into vesicles via hydrophobic interactions between protein molecules under appropriate pH values, which may present great potential in drug-delivery applications . Li et al developed a hydrogel formed via self-assembly of a glycopeptide through enzymatic action of alkaline phosphatase, which can work as an effective matrix to trigger the generation of blood capillaries .…”
Section: Introductionmentioning
confidence: 99%